2011
DOI: 10.1021/pr2005296
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of the Influence of Iron Availability on Cryptococcus gattii

Abstract: Iron is essential and ubiquitous in living organisms. The competition for this micronutrient between the host and its pathogens has been related to disease establishment. Cryptococcus gattii is an encapsulated yeast that causes cryptococcosis mainly in immunocompetent individuals. In this study, we analyzed the proteomic profile of the C. gattii R265 Vancouver Island isolate under iron-depleted and –replete conditions by Multidimensional Protein Identification Technology (MudPIT) and by 2D-GE. Proteins and key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 107 publications
2
15
0
Order By: Relevance
“…The identification of the proteins aconitase (an enzyme involved in the metabolism of carbohydrates) and Wos2 (a cochaperone of Hsp90) corroborates the results of a study by Crestani et al [73], which showed that aconitase and Wos2 expression levels increase in C. gattii (strain R265) in response to a lack of iron in the culture medium. It is important to note that the common factors between our study and that of Crestani et al [73] are the stress conditions to which C. gattii was exposed and that Wos2 has been suggested to be an early marker of C. gattii infection in koalas [56].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The identification of the proteins aconitase (an enzyme involved in the metabolism of carbohydrates) and Wos2 (a cochaperone of Hsp90) corroborates the results of a study by Crestani et al [73], which showed that aconitase and Wos2 expression levels increase in C. gattii (strain R265) in response to a lack of iron in the culture medium. It is important to note that the common factors between our study and that of Crestani et al [73] are the stress conditions to which C. gattii was exposed and that Wos2 has been suggested to be an early marker of C. gattii infection in koalas [56].…”
Section: Discussionsupporting
confidence: 87%
“…It is important to note that the common factors between our study and that of Crestani et al [73] are the stress conditions to which C. gattii was exposed and that Wos2 has been suggested to be an early marker of C. gattii infection in koalas [56]. Similar to enolase, the protein cofilin identified herein may play a relevant role in the process of the fungus spreading to the CNS.…”
Section: Discussionsupporting
confidence: 62%
“…30 Proteins were solubilized by vortexing five times for 1 min each at intervals of 1 min on ice and centrifuged (13 000 rpm for 20 min). Supernatants were collected, and the remaining cell debris were suspended in the same buffer, followed by the same protocol.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…[40]. Samples were then suspended in the buffer containing 50 mM Tris–HCl, pH 7.5, 1 mM EDTA, 1 mM PMSF.…”
Section: Methodsmentioning
confidence: 99%